(untitled) (Journal of the College of Basic Education, 2022)
The research aims to identify the nature of the relationship between post-traumatic stress disorders and violent behavior among primary school students. The researcher built two tools: the post-traumatic stress disorder scale, which consists of two parts: the first part is diagnostic and consists of (14) items, and the second part is used for measurement and consists of (32) items.